Estudio de la población ocupada según rama de la actividad económica y condición de pobreza en el Perú periodo 2019 – 2023 - Silva Torres, Mariliquiz (2025)
There is no more effective way to combat poverty than through the generation of employment, an activity that will lead to income, hence public policies must be called to generate the conducive environment so that private companies can create these jobs. The current master's thesis aims to analyze the branch of economic activity that concentrates the employed population according to the poverty situation in Peru, in the period 2019 - 2023; This Quantitative – Descriptive research, with a Non-Experimental design, was carried out with this objective. It is concluded that the working population living in poverty has been working in greater numbers in the Agriculture/Fishing/Mining activity, with an average of 1,793,870.00 people, which is equivalent to 47.62% of the total. Likewise, workers in extreme poverty carry out their work activity massively in the Agriculture/Fishing/Mining branch (71.45%), concentrating on average 462,890.00 people. For their part, workers in monetary vulnerability were also employed in greater numbers in Agriculture/Fishing/Mining, totaling 2,113,387.00 individuals, which means 37.51% of the total. Unlike non-poor workers, who worked mainly in the branch of activity called Services, considered tertiary, with 4,237,998.00 people, which is equivalent to 32.47% of the total.